Acceptance and commitment therapy for late-life treatment-resistant generalised anxiety disorder: a feasibility study. (13th April 2021) - Gould, Rebecca L; Wetherell, Julie Loebach; Kimona, Kate; Serfaty, Marc A; Jones, Rebecca; Graham, Christopher D; Lawrence, Vanessa; Livingston, Gill; Wilkinson, Philip; Walters, Kate; Le Novere, Marie; Leroi, Iracema; et al.
Abstract: Background: Generalised anxiety disorder (GAD) is the most common anxiety disorder in older people. First-line management includes pharmacological and psychological therapies, but many do not find these effective or acceptable. Little is known about how to manage treatment-resistant generalised anxiety disorder (TR-GAD) in older people. Objectives: To examine the acceptability, feasibility and preliminary estimates of the effectiveness of acceptance and commitment therapy (ACT) for older people with TR-GAD. Participants: People aged ≥65 years with TR-GAD (defined as not responding to GAD treatment, tolerate it or refused treatment) recruited from primary and secondary care services and the community. Intervention: Participants received up to 16 one-to-one sessions of ACT, developed specifically for older people with TR-GAD, in addition to usual care. Measurements: Co-primary outcomes were feasibility (defined as recruitment of ≥32 participants and retention of ≥60% at follow-up) and acceptability (defined as participants attending ≥10 sessions and scoring ≥21/30 on the satisfaction with therapy subscale). Secondary outcomes included measures of anxiety, worry, depression and psychological flexibility (assessed at 0 and 20 weeks). Results: Thirty-seven participants were recruited, 30 (81%) were retained and 26 (70%) attended ≥10 sessions. A total of 18/30 (60%) participants scored ≥21/30 on the satisfaction with therapy subscale. There was preliminary evidence suggesting that ACT may improve anxiety, depression and psychological flexibility. Conclusions: There was evidence of good feasibility and acceptability, although satisfaction with therapy scores suggested that further refinement of the intervention may be necessary. Results indicate that a larger-scale randomised controlled trial of ACT for TR-GAD is feasible and warranted.